PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA KEUANGAN PEMERINTAH KOTA MANADO - Fryane Lolowang, Deiby; Pangkey, Itje; Kantohe, Meidy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The objective of this study is to examine the effect of accountability and transparency on the financial performance of the Manado City Government. This research employs a quantitative approach, utilizing primary data collected through questionnaires distributed to regional apparatuses with budget implementation documents (DPA) of the Regional Budget (APBD) in the Manado City Government. The analysis used in this study involves inferential statistical analysis using Smart Partial Least Square (PLS). Based on the analysis results, it can be concluded that accountability has a positive partial effect on the financial performance of the Manado City Government, meaning that the higher the accountability variable, the better the financial performance. Similarly, transparency has a positive effect on financial performance, indicating that the higher the transparency variable, the better the financial performance of the Manado City Government. Accountability and transparency, collectively (simultaneously), have a positive and significant effect on the financial performance of the Manado City Government.